World’s soils are under threat - Montanarella, Luca; Pennock, D.J.; McKenzie, N.; Badraou, M.; Chude, V.; Baptista, I.; Mamo, T.; Yemefack, Martin; Aulakh, M.S.; Yagi, K.; Hong, S.Y.; Vijarnsorn, P.; et al. (Copernicus GmbH, 2016)
The Intergovernmental Technical Panel on Soils has completed the first State of the World's Soil Resources Report. Globally soil erosion was identified as the gravest threat, leading to deteriorating water quality in developed regions and to lowering of crop yields in many developing regions. We need to increase nitrogen and phosphorus fertilizer use in infertile tropical and semi-tropical soils – the regions where the most food insecurity among us are found – while reducing global use of these products overall. Stores of soil organic carbon are critical in the global carbon balance, and national governments must set specific targets to stabilize or ideally increase soil organic carbon stores. Finally the quality of soil information available for policy formulation must be improved – the regional assessments in the State of the World's Soil Resources Report frequently base their evaluations on studies from the 1990s based on observations made in the 1980s or earlier.